A novel cyclometalated Ir(iii) complex based luminescence intensity and lifetime sensor for Cu2+. Issue 20 (9th February 2016) - Shen, Wei; Qi, Zhengjian; Yan, Liqiang; Tian, Wenwen; Cui, Xia; Yao, Hongtao; Sun, Yueming
Abstract : A novel green luminescent complex [Ir(dfppy)2 (bpy-BiDPA)]PF6 was prepared for the reversible detection of Cu 2+ . Abstract : We report the synthesis and characterization of two luminescent cyclometalated Ir(iii ) complexes [Ir(dfppy)2 (bpy-DPA)]PF6 (Ir-1 ) and [Ir(dfppy)2 (bpy-BiDPA)]PF6 (Ir-2 ), where dfppy, bpy-DPA and bpy-BiDPA represent 2-(2, 4-difluorophenyl)pyridine, N -([2, 2′-bipyridine]-4-yl)-2-(bis(pyridin-2-ylmethyl)amino)acetamide and N, N ′-([2, 2′-bipyridine]-4, 4′-diyl)bis(2-(bis(pyridin-2-ylmethyl)amino)acetamide), respectively. Their photophysical properties and sensing properties towards various metal ions were investigated at room temperature. The two complexes both possessed good photophysical properties, andIr-2 had quite a high quantum yield (93.83%) and a long lifetime (101.17 μs), which is impressive among Ir(iii ) complexes.Ir-2 exhibited both high selectivity and sensitivity towards Cu 2+ over other metal ions. The Job curve and mass spectra suggested the formation of a 1 : 2 bonding mode betweenIr-2 and Cu 2+ . The photoluminescence (PL) intensity quenching curve indicated thatIr-2 could enable rapid and reversible detection of Cu 2+ with a low detection limit of 0.85 ppb (13 nM). Furthermore, a linear relationship could be observed between the PL lifetime value ofIr-2 and the concentration of Cu 2+ ions in the range of 0–8 μM. These results suggested thatIr-2 might have use as not only a promising photoluminescence intensity sensor, but also a promising lifetime sensor for Cu 2+ in aqueous solution.